Contemporary California architects - Jodidio, Philip (Taschen, 1996)
Steel Cloud, West Coast Gateway, Los [angeles (proyecto) / ASYMPTOTE ; Bris Restaurant, Venice / CENTRAL OFFICE OF ARCHITECTURE ; Canyon house, Santa Monica Canyon / CIGOLLE & COLEMAN ; Ehrman-Coombs Residence, Santa Monica - Schulman Residence, Brentwood - Hempstead Residence, Venice / STEVEN EHRLICH ; Schnabel House, Brentwood - Disney Concert Hall, Los Angeles (proyecto) / FRANK O. GEHRY ; Sonoma Coast Residence, Stewarts Point / JOAN HALLBERG ; Towell temporary library, UCLA, Los Angeles / HODGETTS + FUNG ; Goldberg-Bean residence, Hollywood Hills - Art pavilion, Bevery Hills - Fine Arts Building, University of California, Riverside / FRANKLIN ISRAEL ; UCLA Cliller Plant/Facilities Complex, Los Angeles - High Sierras Cabins, Hope Vallery / WES JONES ; Blades residence; Goleta (proyecto) / MORPHOSIS ; The Box, Culver City - IRS Building, Culver City / ERIC OWEN MOSS;Sidley residence, Malibu - Goodson residence, Malibu/ EDWARD R. NILES ; Qwfk house, New Jersey Carson-Reges residence, Los Angeles / ROTO ; The Monument, Joshua Tree / SCHWEITZER BIM